2013
DOI: 10.2478/s13533-012-0124-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining SPOT 5 imagery with plotwise and standwise forest data to estimate volume and biomass in mountainous coniferous site

Abstract: Abstract:In this study, regression-based prediction of volume and aboveground biomass (AGB) of coniferous forests in a mountain test site was conducted. Two datasets -one with applied topographic correction and one without applied topographic correction -consisting of four spectral bands and six vegetation indices were generated from SPOT 5 multispectral image. The relationships between these data and ground data from field plots and national forest inventory polygons were examined. Strongest correlations of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…The results of geographical weighted regression analysis in this study showed that among all the variables, only the ΔExGR index had a significant relationship with carbon sequestration. The result of this study is congruent with findings from other studies, such as (Clerici et al, 2016;Dimitrov & Roumenina, 2013;Günlü et al, 2014;Kumar et al, 2016;Sarker & Nichol, 2011;Terakunpisut et al, 2007;Zhou et al, 2013;Y. Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The results of geographical weighted regression analysis in this study showed that among all the variables, only the ΔExGR index had a significant relationship with carbon sequestration. The result of this study is congruent with findings from other studies, such as (Clerici et al, 2016;Dimitrov & Roumenina, 2013;Günlü et al, 2014;Kumar et al, 2016;Sarker & Nichol, 2011;Terakunpisut et al, 2007;Zhou et al, 2013;Y. Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies deal with accuracy and issues such as, extracting better information from satellite images, aerial photographs and other remote sensing data sources [63][64][65][66][67]. Some studies also discuss how classifications of satel- [68] who also discussed how to improve the accuracy of land cover classification of LANDSAT data and they were able to improve accuracy by incorporating additional data (DEM, spatial texture, NDVI etc.…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant issues to consider when estimating forest AGB over montane areas are still practical problems (Dimitrov and Roumenina, 2013;Sarker et al, 2012). One important practical issue for both parametric and non-parametric methods is the requirement of having sufficient sample plots that represent forest AGB grades and the requirement for precise geo-referencing within the study area (Gilichinsky et al, 2012;Hill et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this treatment can reduce the overcorrection of faintly illuminated pixels (Soenen et al, 2005;Dimitrov and Roumenina, 2013). In this chapter, the constant, C τ was only added for coniferous forests (Picea crassifolia).…”
Section: The Scs+c Radiometric Terrain Correctionmentioning
confidence: 99%